Impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in the Nervous System: Implications of COVID-19 in Neurodegeneration - Rodriguez, Myosotys; Soler, Yemmy; Perry, Marissa; Reynolds, Jessica L.; El-Hage, Nazira (Frontiers in Neurology, 2020)
Coronavirus Disease 2019 (COVID-19), caused by the Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2), began in December 2019, in Wuhan, China and was promptly declared as a pandemic by the World Health Organization (WHO). As an acute respiratory disease, COVID-19 uses the angiotensin-converting enzyme 2 (ACE2) receptor, which is the same receptor used by its predecessor, SARS-CoV, to enter and spread through the respiratory tract. Common symptoms of COVID-19 include fever, cough, fatigue and in a small population of patient SARS-CoV-2 can cause several neurological symptoms. Neurological malaise may include severe manifestations, such as acute cerebrovascular disease and meningitis/encephalitis. Although there is evidence showing that coronaviruses can invade the central nervous system (CNS), studies are needed to address the invasion of SARS-CoV-2 in the CNS and to decipher the underlying neurotropic mechanisms used by SARS-CoV-2. This review summarizes current reports on the neurological manifestations of COVID-19 and addresses potential routes used by SARS-CoV-2 to invade the CNS.